An inexpensive point-of-care immunochromatographic test for Talaromyces marneffei infection based on the yeast phase specific monoclonal antibody 4D1 and Galanthus nivalis agglutinin. - Kritsada Pruksaphon; Akarin Intaramat; Pavinee Simsiriwong; Skorn Mongkolsuk; Kavi Ratanabanangkoon; Joshua D Nosanchuk; Anna Kaltsas; Sirida Youngchim (PLoS Neglected Tropical Diseases)
Talaromyces marneffei is a thermally dimorphic fungus that causes opportunistic systemic mycoses in patients with AIDS or other immunodeficiency syndromes. The purpose of this study was to develop an immunochromatographic strip test (ICT) based on a solid phase sandwich format immunoassay for the detection of T. marneffei antigens in clinical urine specimens. The T. marneffei yeast phase specific monoclonal antibody 4D1 (MAb4D1) conjugated with colloidal gold nanoparticle was used as a specific signal reporter. Galanthus nivalis Agglutinin (GNA) was adsorbed onto nitrocellulose membrane to serve as the test line. Similarly, a control line was created above the test line by immobilization of rabbit anti-mouse IgG. The immobilized GNA served as capturing molecule and as non-immune mediated anti-terminal mannose of T. marneffei antigenic mannoprotein. The MAb4D1-GNA based ICT showed specific binding activity with yeast phase antigen of T. marneffei, and it did not react with other common pathogenic fungal antigens. The limit of detection of this ICT for T. marneffei antigen spiked in normal urine was approximately 0.6 μg/ml. The diagnostic performance of the ICT was validated using 341 urine samples from patents with culture- confirmed T. marneffei infection and from a control group of healthy individuals and patients with other infections in an endemic area. The ICT exhibited 89.47% sensitivity, 100% specificity, and 97.65% accuracy. Our results demonstrate that the urine-based GNA-MAb4D1 based ICT produces a visual result within 30 minutes and that the test is highly specific for the diagnosis of T. marneffei infection. The findings validate the deployment of the ICT for clinical use.